EFEKTIVITAS USAHA MIKRO DALAM PENINGKATAN KESEJAHTERAAN EKONOMI MASYARAKAT - Noorma Yunia; Setyabudi Daryono; Ilmi Albadiah; Euis Ajizah; Ade Sahruroji (STAI La Tansa Mashiro, 2026)
The existence of the Mawar Donut microenterprise has also been very helpful in alleviating social welfare issues and can help reduce the unemployment rate in the region. On the other hand, the microenterprise is also able to absorb labor in the region, thereby reducing the unemployment rate. To determine the effectiveness of the Mawar Donut microenterprise, To determine the effectiveness of the Mawar Donut microenterprise in improving economic well-being, qualitative research—which is designed to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, and the thoughts of individuals or groups—uses a case study approach. Qualitative data is typically collected through various methods, such as interviews and observation. fieldwork, and documentation. Data collection techniques included observation, interviews, and documentation. The results of the study on Mawar Donat showed that the interview with Mrs. Ulfah Khofifah, the owner of the Mawar Donat shop, was effective in improving the well-being of the community surrounding the shop. Its location within a specific area—including the school zone—has boosted the prosperity of the Mawar Donat business and supported the local economy in general, making Mawar Donat a business that caters to the needs of every customer, whether for resale or for daily consumption.